B cells undergo unique compartmentalized redistribution in multiple sclerosis - Haas, Jürgen; Bekeredjian-Ding, Isabelle; Milkova, Miriam; Balint, Bettina; Schwarz, Alexander; Korporal-Kuhnke, Mirjam; Jarius, Sven; Fritz, Brigitte; Lorenz, Hanns-Martin; Wildemann, Brigitte (Journal of autoimmunity, 2011)
Increasing evidence fosters the role of B cells (BC) in multiple sclerosis (MS). The compartmentalized distribution of BC in blood and cerebrospinal fluid (CSF) is incompletely understood. In this study, we analyzed BC-patterns and BC-immunoreactivity at these sites during active and during stable disease and the impact of disease modifying drugs (DMD) on peripheral BC-homeostasis. For this purpose we assessed BC-subsets in blood and CSF from patients with clinically isolated syndrome (CIS), relapsing remitting MS (RRMS), rheumatoid arthritis (RA), and healthy controls (HC) by flow cytometric detection of whole (W-BC), naïve, transitional (TN-BC), class-switched memory (CSM-BC), unswitched memory (USM-BC), double-negative memory (DNM-BC) BC-phenotypes, plasma blasts (PB), and plasma cells (PC). FACS-data were correlated with BC-specific chemotactic activities in CSF, intrathecal CXCL13-levels, and immunoreactivity of peripheral W-BC. Our study revealed that frequencies of systemic CSM-BC/USM-BC became contracted in active CIS/MS while proportions of naive BC, TN-BC and DNM-BC were reciprocally expanded. Moreover, the shifted BC-composition promoted reduced immunoreactivity of W-BC and resolved during remission. Cross-over changes in CSF included privileged accumulation of CSM-BC linked to intrathecal CXCL13-concentrations and expansion of PB/PC. Treatment with interferon-beta and natalizumab evoked distinct though differing redistribution of circulating BC-subsets. We conclude that symptomatic CIS and MS are accompanied by distinctive changes in peripheral and CSF BC-homeostasis. The privileged reciprocal distribution between naïve versus CSM-phenotypes in both compartments together with the marked chemotactic driving force towards BC prompted by CSF supernatants renders it likely that CSF BC are mainly recruited from peripheral blood during active CIS/MS, whereas constantly low percentages of circulating PB/PC and their failure to respond to migratory stimuli favors intrathecal generation of antibody secreting cells. Notably, BC-redistribution closely resembles alterations detectable in systemic autoimmunity associated with active RA and impacts BC-function Together with unique effects of DMDs on BC-homeostasis these findings underline the important role of BC in MS.